Anonymous collections: the everyday the hidden, the strange - Puebla Cardenas, Omar (2018)
This investigation reflects on the capacity of massive objects to break with the consumption-use-waste chain, and later, to become containers of individual stories and memories, acquiring new uses, meanings, and even changing their appearance. What we see in everyday objects (appearance and functionality) is just the tip of the iceberg; there is in each of them “something” that goes beyond simply fulfilling its initial purpose; However, this “new life” is only possible when they come into contact with those who give them the opportunity to leave their crowded world and become unique: the collector. The study that follows presents a possible classification of this type of objects, depending on the use that their owners give them after having fulfilled their “useful life”. We chose ten people to exhibit this type of objects in the showcases of their homes, because this piece of furniture guarantees that its owner did not want to get rid of it and collects it. From our “findings”, we made a “taxonomy”, presenting a top 10 of the most popular objects that live behind a glass in certain homes in the city of Quito